Ocular inflammatory events following COVID-19 vaccination: a multinational case series - Testi, Ilaria (2022)
Background: Inflammatory adverse events following COVID-19 vaccination are being reported amidst the growing concerns regarding vaccine’s immunogenicity and safety, especially in patients with pre-existing inflammatory conditions. Methods: Multinational case series of patients diagnosed with an ocular inflammatory event within 14 days following COVID-19 vaccination collected from 40 centres over a 3 month period in 2021. Results: Seventy patients presented with ocular inflammatory events within 14 days following COVID-19 vaccination. The mean age was 51 years (range, 19–84 years). The most common events were anterior uveitis (n = 41, 58.6%), followed by posterior uveitis (n = 9, 12.9%) and scleritis (n = 7, 10.0%). The mean time to event was 5 days and 6 days (range, 1–14 days) after the first and second dose of vaccine, respectively. Among all patients, 36 (54.1%) had a previous history of ocular inflammatory event. Most patients (n = 48, 68.6%) were managed with topical corticosteroids. Final vision was not affected in 65 (92.9%), whereas 2 (2.9%) and 3 (4.3%) had reduction in visual acuity reduced by ≤3 lines and > 3 lines, respectively. Reported complications included nummular corneal lesions (n = 1, 1.4%), cystoid macular oedema (n = 2, 2.9%) and macular scarring (n = 2, 2.9%). Conclusion: Ocular inflammatory events may occur after COVID-19 vaccination. The findings are based on a temporal association that does not prove causality. Even in the possibility of a causal association, most of the events were mild and had a good visual outcome.